2020
DOI: 10.3390/ma13051174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solidification Conditions on the Microstructure of Laser-Surface-Melted Ductile Cast Iron

Abstract: The thermal conditions in the molten pool during the laser surface melting of ductile cast iron EN-GJS-700-2 were estimated by using infrared thermography and thermocouple measurements. The thermal data were then correlated with the microstructure of the melted zone. Additionally, the thermodynamic calculations of a Fe-C-Si alloy system were performed to predict the solidification path of the melted zone. It was found that increasing the cooling rate during solidification of the refined ledeburite eutectic but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
11
0
4
Order By: Relevance
“…Other than LBW, multiple research efforts with a focus on enhanced erosion resistance of grey cast iron with spheroidal graphite through laser surface melting have been made, e.g., by Janicki [15,16]. It was found that surface melting of nodular grey cast iron yielded hardness values of up to 1000 HV in non-porous layers.…”
Section: Introductionmentioning
confidence: 99%
“…Other than LBW, multiple research efforts with a focus on enhanced erosion resistance of grey cast iron with spheroidal graphite through laser surface melting have been made, e.g., by Janicki [15,16]. It was found that surface melting of nodular grey cast iron yielded hardness values of up to 1000 HV in non-porous layers.…”
Section: Introductionmentioning
confidence: 99%
“…Lasers as a heat source have been widely applied in industrial processes [1,2]. Currently, they are used for welding, cutting, remelting, and various processes with surface modification of materials [3][4][5][6]. Laser sources are characterized by: high energy density, high efficiency, large temperature gradients, high repeatability of the process, and formation of a narrow heat affected zone (HAZ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 , 8 , 9 ]. The area of application of various technological laser solutions includes processing of many types of metals and their alloys, ceramics, polymers, and composites [ 1 , 5 , 10 , 11 ], including underwater local dry welding and wet welding [ 12 , 13 ]. Limiting the disadvantageous effects of technological use of lasers in some applications, e.g., the small width of weld, can be obtained by combining it with other heat sources to create hybrid processes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the “DNV-RP-C201 Recommended Practice—Environmental Conditions and Environmental Loads” standard [ 9 ], environmental conditions affect design and technological decisions on which the life of the structure depends. This applies to the properties of the materials used and their joining technologies, including welding processes [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%